Spatial Characteristics of Art Trade in Hungary - Ibolya Várnai (DETUROPE)
Century-long traditons of art trade in Hungary are strongly connected to the capital, famous, elite auction houses and galleries are concentrated in the downtown area of Budapest. Although art market in Hungary is capital-centered, remarkable amount of art trade takes place in the countryside too. This study aims to give insight into the presence of the different types of art trade (antique shops, second-hand book stores, art galleries and auction houses) in rural settlements, compared to the characteristics of art trade in Budapest. The research – based on primary data collection – reveals the social, economic, and cultural factors which explain the regional differences in art trade. During the field work in Budapest, semi-structured interviews were conducted with art gallery owners, auctioners, and antiquarians. The penetration index (PEX) which was applied in the case of researches in the countryside shows the rate in which the different types of art trade are present in settlements of different sizes. The results are demonstrated on the map with the help of the Mapinfo 12.5 software.